Elucidating the Trends in Reactivity of Aza‐1, 3‐Dipolar Cycloadditions. Issue 2 (21st August 2018) - Hamlin, Trevor A.; Svatunek, Dennis; Yu, Song; Ridder, Lars; Infante, Ivan; Visscher, Lucas; Bickelhaupt, F. Matthias
Abstract : This report describes a density functional theory investigation into the reactivities of a series of aza‐1, 3‐dipoles with ethylene at the BP86/TZ2P level. A benchmark study was carried out using QMflows, a newly developed program for automated workflows of quantum chemical calculations. In total, 24 1, 3‐dipolar cycloaddition (1, 3‐DCA) reactions were benchmarked using the highly accurate G3B3 method as a reference. We screened a number of exchange and correlation functionals, including PBE, OLYP, BP86, BLYP, both with and without explicit dispersion corrections, to assess their accuracies and to determine which of these computationally efficient functionals performed the best for calculating the energetics for cycloaddition reactions. The BP86/TZ2P method produced the smallest errors for the activation and reaction enthalpies. Then, to understand the factors controlling the reactivity in these reactions, seven archetypal aza‐1, 3‐dipolar cycloadditions were investigated using the activation strain model and energy decomposition analysis. Our investigations highlight the fact that differences in activation barrier for these 1, 3‐DCA reactions do not arise from differences in strain energy of the dipole, as previously proposed. Instead, relative reactivities originate from differences in interaction energy. Analysis of the 1, 3‐dipole–dipolarophile interactions reveals the reactivity trends primarily result from differences in the extent of the primary orbital interactions. Abstract : Trace it back to the source! A full account of the reactivity of a series of aza‐1, 3‐dipoles in cycloadditions is reported using a newly benchmarked method (BP86/TZ2P). We employ activation strain analyses to understand the factors governing reaction rates and highlight the importance of orbital interactions, as opposed to strain energy, in determining reactivity!